1996
DOI: 10.1128/jb.178.18.5395-5401.1996
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic switching of variable surface lipoproteins in Mycoplasma bovis involves high-frequency chromosomal rearrangements

Abstract: Mycoplasma bovis, an important pathogen of cattle, was recently shown to possess a family of phase-and size-variable membrane surface lipoprotein antigens (Vsps). These proteins spontaneously undergo noncoordinate phase variation between ON and OFF expression states, generating surface antigenic variation. In the present study, we show that the spontaneously high rate of Vsp phenotypic switching involves DNA rearrangements that occur at high frequency in the M. bovis chromosome. A 1.5-kb HindIII genomic fragme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
157
0

Year Published

2002
2002
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 115 publications
(159 citation statements)
references
References 40 publications
2
157
0
Order By: Relevance
“…This result is not surprising because this primer set targets conserved motives flanking tandem repeat regions, which are known to vary in the number of repeats, at least between the M. bovis reference strain PG45 T and field strain 422. Moreover, different repertoires of Vsp genes have been observed in M. bovis, 23,29,37 and primer set B can potentially amplify at least Vsp 422-4 and Vsp 422-8 in strain 422. Sequencing of vsp A revealed that Sar1 is characterized by a number of R A tandem repeats in the initial portion of the Vsp A -like gene (10 repeats, 8 R A 1 and 2 R A 2) that is different from the number observed in the strains so far described (Table 4).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This result is not surprising because this primer set targets conserved motives flanking tandem repeat regions, which are known to vary in the number of repeats, at least between the M. bovis reference strain PG45 T and field strain 422. Moreover, different repertoires of Vsp genes have been observed in M. bovis, 23,29,37 and primer set B can potentially amplify at least Vsp 422-4 and Vsp 422-8 in strain 422. Sequencing of vsp A revealed that Sar1 is characterized by a number of R A tandem repeats in the initial portion of the Vsp A -like gene (10 repeats, 8 R A 1 and 2 R A 2) that is different from the number observed in the strains so far described (Table 4).…”
Section: Discussionmentioning
confidence: 99%
“…This number is lower than the number of repeats of the type strain PG45 T , but higher than the number reported for M. bovis strain 422. 23,29 When vsp A PCR (primer set B) was used to compare Sar1 to M. bovis field strains isolated in northern and central Italy, it was observed that the Sar1 PCR pattern (Fig. 1B, lane 3, 1 band of about 340 bp) is different from the pattern formed by the northern Italy strains (Fig.…”
Section: Isolation Of Mycoplasmas and Routine Microbiological Investimentioning
confidence: 99%
See 1 more Smart Citation
“…However, only one vsa gene is expressed, while the others are transcriptionally silent (45). Structurally, the expressed vsa gene displays features similar to the vlp and the vsp genes (267,485). The expressed vsa gene is divided into three regions: region I, encoding a putative lipoprotein signal sequence; region II, the region encoding the conserved N terminus of the mature Vsa protein; and region III, a variable region containing the 3Ј repetitive elements (45,421).…”
Section: Gene Families As a Common Theme For Surface Diversificationmentioning
confidence: 99%
“…Mycoplasma bovis, an important pathogen of cattle, presents another interesting example. A family of proteins undergoing noncoordinate high-frequency phase variation, as well as size variation (designated Vsps), is used to achieve extensive antigenic variation (34,267,268,387). Thirteen Vsp ORFs, not all similarly oriented, were identified within a 16-kb genomic fragment carrying the vsp locus (268).…”
Section: Gene Families As a Common Theme For Surface Diversificationmentioning
confidence: 99%